Branding America: An Examination of U.S. Public Diplomacy Efforts After September 11, 2001 - Tiedeman, Anna K. (Tufts Archival Research Center, 2007)
Submitted in partial fulfillment of the degree Master of Arts in Law and Diplomacy at the Fletcher School of Law and Diplomacy. Abstract: This paper explores the public diplomacy efforts of the United States after September 11, 2001 within the context of public diplomacy theory to make the case that the application of the private sector marketing technique of branding was not the sole reason the campaigns failed. Using the efforts of Under Secretary of State Charlotte Beers as a case study, I will explain why her case proves the U.S. needs to dramatically shift its public diplomacy efforts from crisis management in the Middle East to a global emphasis on building relationships in the future. In this paper, I explore the concepts of public diplomacy and branding to uncover the similarities that may have proved useful and the differences that may have spelled disaster ultimately concluding that the failure of the public diplomacy campaigns under Beers had less to do with the application of branding techniques to public policy and more to do with institutional, cultural and political factors. The paper concludes with prescriptions for the future conduct of U.S. public diplomacy advocating the need to take a long-term global perspective and to back away from short term myopically focused crisis management in a region where the U.S. Government is not a credible messenger. To restore this lost credibility, a two-way system of communication and understanding needs to be implemented through public diplomacy around the world.